The Life of the Particle: José Torrubia and the Vital Mechanics of Matter - Hill, Ruth (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2022)
This essay explores vitalism in José Torrubia's Aparato para la historia natural de España (1754), a work cited by renowned Enlightenment paleontologists and mineralogists. Torrubia is absent from scholarly accounts of vitalism, which exclude Spain and its colonial territories from scientific modernity. His vitalism turned on how and why he distinguished "dead" matter from "live" matter. As a natural historian and missionary, he travelled throughout Europe, Peru, and Mexico, exchanging artifacts and ideas with Enlightenment figures from France, Germany, and Italy. Aparato offers us today a broader perspective on Enlightenment and postmodern strands of vitalism.